Symposium of Materials Science and Chemistry III Selected, peer-reviewed papers from the 6th International Conference on Science and Technology (ICST 2020), September 7-8, 2020, Yogyakarta, Indonesia - Kusumaatmaja, Ahmad; Wahyuningsih, Tutik Dwi; Khairuddean, Melati; Kartini, Indriana; Roto, Roto; Ohto, Keisuke; Siswanta, Dwi; Motuzas, Julius; Natsir, Taufik Abdillah (Trans Tech Publications, Limited, 2021)
Selected peer-reviewed full text papers from the 6th International Conference on Science and Technology (ICST 2020) Selected, peer-reviewed papers from the 6th International Conference on Science and Technology (ICST 2020), September 7-8, 2020, Yogyakarta, Indonesia.
Description based upon print version of record.
Keywords: Materials science -- Congresses.; Chemistry -- Congresses.; Materials science -- Research -- Congresses.; Technology -- Congresses.; Absorption -- Congresses.; Agriculture -- Congresses.; Biomedical materials -- Congresses.; Bone regeneration -- Congresses.; Density functionals -- Congresses.; Direct methanol fuel cells -- Congresses.; Environmental engineering -- Congresses.; Fermentation -- Congresses.; Hydroxyapatite -- Congresses.; Mordenite -- Congresses.; Nanostructured materials -- Congresses.; Particle board -- Congresses.; Pharmacology -- Congresses.; Lightweight concrete -- Congresses.; Thin films -- Congresses.; elektronické knihy; electronic books